How audio-visual stimuli in automated asynchronous video interviews affect applicant reactions: social presence, fairness and organisational attractiveness - Patel, Ahmed (Organisational Psychology, 2023)
Over the past decade, the use of asynchronous video interviews (AVIs) has increased exponentially, largely spurred by ongoing technological progress and shifts to remote work. Although prior research shows interview design can influence applicant reactions, the effect of video interview design factors on interviewee reactions remains unclear. The present study determines the influence of AVI stimulus format (text-based vs. audio-visual questions) on applicant perceptions of social presence, fairness and organisational attractiveness. To this end, a between-subjects posttest-only experimental design was used in two separate samples (South African sample, N = 58; USA sample, N = 169, Combined samples, N = 227). Participants were randomly assigned to either the control or experimental group. Participants completed a mock interview on a commercially available AVI platform and then answered a questionnaire measuring perceptions of social presence, fairness, and organisational attractiveness. Bootstrapped independent sample t-tests and serial mediation were used to test the hypotheses. Within Sample 1, applicant perceptions of social presence, fairness and organisational attractiveness were higher for the audio-visual and text-based AVIs, thereby supporting the proposition that audio-visual stimuli lead to higher perceptions of social presence, fairness and organisational attractiveness. Conversely, Sample 2's findings were non-significant (p > .05). While there were mixed results, the findings of this study provide preliminary evidence which suggests that within the South African context, audio-visual stimuli can be used in AVIs. Organisations in the American context should pay close attention to the effects of AVI stimulus format on applicant reactions as the findings from the American sample were not conclusive. Future research should investigate applicant reactions to different forms of AVI stimulus during a multi-stage selection process